2020
DOI: 10.1083/jcb.202005035
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-wide coordination of epithelium-to-neural stem cell transition in the Drosophila optic lobe requires Neuralized

Abstract: Many tissues are produced by specialized progenitor cells emanating from epithelia via epithelial-to-mesenchymal transition (EMT). Most studies have so far focused on EMT involving single or isolated groups of cells. Here we describe an EMT-like process that requires tissue-level coordination. This EMT-like process occurs along a continuous front in the Drosophila optic lobe neuroepithelium to produce neural stem cells (NSCs). We find that emerging NSCs remain epithelial and apically constrict before dividing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
(129 reference statements)
2
6
0
Order By: Relevance
“…Indeed, in Drosophila, Crb can act both as a positive regulator and as a negative regulator of ROCK-mediated actomyosin contractility. aPKC, Pak1, and Moesin have all been implicated as downstream effectors of Crb in this context [230][231][232][233][234][235]. Taken together, the current data implicate the Crumbs complex in the coordination of Rho-and Cdc42-dependent actomyosin activity at the apical-lateral border.…”
Section: Role Of the Crumbs Complex In Hippo Signaling And The Regula...supporting
confidence: 56%
“…Indeed, in Drosophila, Crb can act both as a positive regulator and as a negative regulator of ROCK-mediated actomyosin contractility. aPKC, Pak1, and Moesin have all been implicated as downstream effectors of Crb in this context [230][231][232][233][234][235]. Taken together, the current data implicate the Crumbs complex in the coordination of Rho-and Cdc42-dependent actomyosin activity at the apical-lateral border.…”
Section: Role Of the Crumbs Complex In Hippo Signaling And The Regula...supporting
confidence: 56%
“…The loss of the Crb complex then precipitates the concurrent loss of the apical membrane and AJs. A similar regulatory interplay between Crb, Sdt, and Neur was also observed during early neurogenesis in the Drosophila optic lobes ( Shard et al, 2020 ). Here, neural stem cells emerge from a wave front in the optic lobes rather than ingress as individual cells.…”
Section: Discussionsupporting
confidence: 54%
“…It is interesting to speculate that these defects in the lamina furrow are due to defects in the neuroepithelial cell remodelling in the absence of Shmt. Interestingly it has also been previously shown that the transition from neuroepithelia to medulla NBs is accompanied by the remodelling of the newly formed NSC, which must apically constrict before dividing ( Shard et al, 2020 ). These NSCs at the transition zone, also called epithelial-like neural stem cell (epi-NSC), apically constrict due to myosin pulses and only afterwards undergo an asymmetric cell division to form an NB, which will then generate a GMC and ultimately neurons ( Shard et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly it has also been previously shown that the transition from neuroepithelia to medulla NBs is accompanied by the remodelling of the newly formed NSC, which must apically constrict before dividing ( Shard et al, 2020 ). These NSCs at the transition zone, also called epithelial-like neural stem cell (epi-NSC), apically constrict due to myosin pulses and only afterwards undergo an asymmetric cell division to form an NB, which will then generate a GMC and ultimately neurons ( Shard et al, 2020 ). Thus, although we observed that fate determinants are still expressed at the transition zone from neuroepithelia to medulla NBs, the defects in the formation of the medulla could also be due to remodelling defects.…”
Section: Discussionmentioning
confidence: 98%